Interactions between Flow Oscillations and Biochemical Parameters in the Cerebrospinal Fluid - Puy, Vincent; Zmudka-Attier, Jadwiga; Capel, Cyrille; Bouzerar, Roger; Serot, Jean-Marie; Bourgeois, Anne-Marie; Ausseil, Jérome; Balédent, Olivier (Frontiers in Aging Neuroscience, 2016)
The equilibrium between the ventricular and lumbar cerebrospinal fluid (CSF) compartments may be disturbed (in terms of flow and biochemistry) in patients with chronic hydrocephalus (CH). Using flow MRI and CSF assays, we sought to determine whether changes in CSF were associated with biochemical alterations. Nine elderly patients with CH underwent phase-contrast MRI. An index of CSF dynamics (Idyn) was defined as the product of the lumbar and ventricular CSF flows. During surgery, samples of CSF were collected from the lumbar and ventricular compartments and assayed for chloride, glucose and total protein. The lumbar/ventricular (L/V) ratio was calculated for each analyte. The ratio between measured and expected levels (Ibioch) was calculated for each analyte and compared with Idyn. Idyn varied from 0 to 100.10-3µl2.s2. In contrast to chloride and glucose, the L/V ratio for total protein varied markedly from one patient to another (mean ± standard deviation: 2.63±1.24). The Ibioch for total protein was strongly correlated with the corresponding Idyn(Spearman’s R: 0.98; p<5x10-5). We observed correlated alterations in CSF flow and biochemical parameters in patients with CH. Our findings also highlight the value of dynamic flow analysis in the interpretation of data on CSF biochemistry.